2017
DOI: 10.1093/ageing/afx099
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-at-home Integrated Care Programme for the management of disabling health crises in older patients: comparison with bed-based Intermediate Care

Abstract: in our study, the extended CGA-based hospital-at-home programme was associated with shorter stay and favourable clinical outcomes. Future studies might test this intervention to the whole Catalan integrated care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
0
31
1
1
Order By: Relevance
“…In the UK, this typically involves a consultation with a primary care practitioner in a practice (also known as a surgery, clinic or community health centre) but in an appointment that is usually too time limited to undertake CGA. Established avenues for onward referral include community-based services that perform in-home CGA assessment such as communitybased geriatric services [11], or secondary care services with review by a geriatrician in an outpatient clinic. There currently appears no established method of assessing these patients within the primary care practice itself.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, this typically involves a consultation with a primary care practitioner in a practice (also known as a surgery, clinic or community health centre) but in an appointment that is usually too time limited to undertake CGA. Established avenues for onward referral include community-based services that perform in-home CGA assessment such as communitybased geriatric services [11], or secondary care services with review by a geriatrician in an outpatient clinic. There currently appears no established method of assessing these patients within the primary care practice itself.…”
Section: Introductionmentioning
confidence: 99%
“…These positive findings are consistent with the findings of previous home-based geriatric rehabilitation studies. 6 8 , 34 …”
Section: Discussionmentioning
confidence: 99%
“… 2 5 A cohort study on orthopedic older patients suggested that home intervention significantly shortened the duration of rehabilitation and enhanced its efficiency ( P <0.01). 6 Two pragmatic randomized controlled trials (RCTs) with similar designs, from the UK (N=250) 7 and Sweden (N=205), 8 suggested that community in-reach rehabilitation and care transition could reduce hospital stay for 2.3 and 6 days, respectively. Effective rehabilitation programs can enhance clients’ physical functioning and mobility through tailored and individualized physical training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that optimal care for frailty and system benefits will not be realised until well coordinated health and social care assessment and support can be accessed across care settings and at all times. We consider this can be facilitated by remote monitoring and decision support in the community and by urgent access to intermediate care or transition services such as Hospital at Home [1617]. …”
Section: Cga + Care Transitionsmentioning
confidence: 99%